Nanostructuring mixed‐dimensional perovskites : a route toward tunable, efficient photovoltaics - Koh, Teck Ming (2020)
2D perovskites is one of the proposed strategies to enhance the moisture resistance, since the larger organic cations can act as a natural barrier. Nevertheless, 2D perovskites hinder the charge transport in certain directions, reducing the solar cell power conversion efficiency. A nanostructured mixed‐dimensionality approach is presented to overcome the charge transport limitation, obtaining power conversion efficiencies over 9%.